2015
DOI: 10.1111/hel.12270
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics on Gut Microbiota during the Helicobacter pylori Eradication: Randomized Controlled Trial

Abstract: Probiotic supplementation can reduce the antibiotic-induced alteration and imbalance of the gut microbiota composition. This effect may restrict the growth of antibiotic-resistant bacteria in the gut and improve the H. pylori eradication success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 39 publications
7
158
3
Order By: Relevance
“…Then, in a study exploring both short-and long-term effects of H. pylori therapy, it has been demonstrated that although the diversity of the microbiota subsequently recovered to resemble the pre treatment states, the microbiota remained perturbed in some cases for up to 4 years post treatment [91]. More recently, as it evidenced by Chun J et al [93], probiotic supplementation can reduce the antibiotic-induced alteration and imbalance of the gut microbiota composition. More recently, as it evidenced by Chun J et al [93], probiotic supplementation can reduce the antibiotic-induced alteration and imbalance of the gut microbiota composition.…”
Section: H Pylori Eradication and The Alterations Of Microbiotamentioning
confidence: 99%
“…Then, in a study exploring both short-and long-term effects of H. pylori therapy, it has been demonstrated that although the diversity of the microbiota subsequently recovered to resemble the pre treatment states, the microbiota remained perturbed in some cases for up to 4 years post treatment [91]. More recently, as it evidenced by Chun J et al [93], probiotic supplementation can reduce the antibiotic-induced alteration and imbalance of the gut microbiota composition. More recently, as it evidenced by Chun J et al [93], probiotic supplementation can reduce the antibiotic-induced alteration and imbalance of the gut microbiota composition.…”
Section: H Pylori Eradication and The Alterations Of Microbiotamentioning
confidence: 99%
“…[76][77][78][79] Bismuth-based quadruple therapy was used in two studies. [76][77][78][79][80][81] Shortly after H pylori eradication therapy, the bacterial diversity was significantly reduced at the end of eradication therapy. [76][77][78][79][80][81] Shortly after H pylori eradication therapy, the bacterial diversity was significantly reduced at the end of eradication therapy.…”
Section: Impac T Of H Pylori Er Adic Ation On G Ut MI Crob I Otamentioning
confidence: 99%
“…80,81 The case numbers are relatively small, ranging from 6 to 70, with a total of 147 cases. [76][77][78][79][80][81] In patients treated with triple therapy, the relative abundance of Firmicutes was reduced, whereas that of Proteobacteria was increased. [76][77][78][79][80][81] In patients treated with triple therapy, the relative abundance of Firmicutes was reduced, whereas that of Proteobacteria was increased.…”
Section: Impac T Of H Pylori Er Adic Ation On G Ut MI Crob I Otamentioning
confidence: 99%
“…Additionally, Emara et al focused on the emerging role of Pbs from a histopathological perspective and found that Pbs lowered H. pylori density on the luminal side of the epithelium, thereby improving the histological inflammatory and activity scores in the gastric corpus and antrum over an extended period (Emara et al, 2016). Moreover, H. pylori eradication influenced the gut microbiota (Jakobsson et al, 2010; Malfertheiner et al, 2016); the addition of Pbs (e.g., Streptococcus faecium and Bacillus subtilis ) to standard triple therapies may restrict the growth of antibiotic-resistant bacteria and reduce the fluctuation of the gut microbiota (Oh et al, 2016). …”
Section: Treatmentmentioning
confidence: 99%